2015
DOI: 10.7314/apjcp.2015.16.12.4873
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors: A Clinicopathologic and Risk Stratification Study of 255 Cases from Pakistan and Review of Literature

Abstract: Purpose: To describe the clinicopathological features of gastrointestinal stromal tumors (GIST) diagnosed in our section and to perform risk stratification of our cases by assigning them to specific risk categories and groups for disease progression based on proposals by Fletcher et al and Miettinen and Lasota. Materials and Results: We retrieved 255 cases of GIST diagnosed between 2003 and 2014. Over 59% were male. The age range was 16 to 83 years with a mean of 51 years. Over 70% occurred between 40 and 70 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…This observation was in agreement with that of Ahmed et al [9], Klieser et al [10], Lopes et al [11] Alqusous et al [12], Vij et al [13], Yacob et al [14], Din et al [16], Li et al [17], Cao et al [18], Sui et al [19], Tazawa et al [20], Kang et al [21], and Kkrishnappa et al [22]. These are in contrast with the two studies of Antonescu et al [7] and Bhalgami et al [15] which found slightly more in the small intestine than stomach.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This observation was in agreement with that of Ahmed et al [9], Klieser et al [10], Lopes et al [11] Alqusous et al [12], Vij et al [13], Yacob et al [14], Din et al [16], Li et al [17], Cao et al [18], Sui et al [19], Tazawa et al [20], Kang et al [21], and Kkrishnappa et al [22]. These are in contrast with the two studies of Antonescu et al [7] and Bhalgami et al [15] which found slightly more in the small intestine than stomach.…”
Section: Discussionsupporting
confidence: 92%
“…GIST is most occurring in old age group. In our study, the mean age of the patients was 61.18 ± 14.13 years which was supported by the observations of Antonescu et al [7], Alqusous et al [12], Din et al [16], and Kkrishnappa et al [22]. The minimum age was 15 years which is similar to the study of Antonescu et al (12 years old).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gastrointestinal stromal tumors (GISTs) are the most common primary mesenchymal tumors of the gastrointestinal tract with varying malignancy potential 1) . To evaluate their biological behavior is significant for the decision making before the surgery 2) .…”
Section: ( II )-2 筋線維走行解析を目的とした人体連続切片標本画像からの筋線維トラク トグラフィーとその定量評価 1.mentioning
confidence: 99%